2017
DOI: 10.5409/wjcp.v6.i2.110
|View full text |Cite
|
Sign up to set email alerts
|

Conversion from prolonged intravenous fentanyl infusion to enteral methadone in critically ill children

Abstract: AIMTo describe our institutional experience with conversion from intravenous (IV) fentanyl infusion directly to enteral methadone and occurrence of withdrawal in critically ill mechanically ventilated children exposed to prolonged sedation and analgesia.METHODSWith Institutional Review Board approval, we retrospectively studied consecutively admitted invasively mechanically ventilated children (0-18 years) sedated with IV fentanyl infusion > 5 d and subsequently converted directly to enteral methadone. Data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Methadone, lorazepam, clonidine, or dexmedetomidine are commonly used as an adjunctive therapy for opioid or benzodiazepine withdrawal. 7 , 15 23 Our study used methadone and lorazepam as primary medications for weaning therapy. Several prior studies demonstrated various opioid weaning strategies by using methadone to prevent opioid withdrawal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Methadone, lorazepam, clonidine, or dexmedetomidine are commonly used as an adjunctive therapy for opioid or benzodiazepine withdrawal. 7 , 15 23 Our study used methadone and lorazepam as primary medications for weaning therapy. Several prior studies demonstrated various opioid weaning strategies by using methadone to prevent opioid withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies showed that 40 to 80% of patients develop IWS. 6 , 23 Several previous studies reviewed the conversion of intravenous fentanyl to oral methadone. The proposed conversion ratio varied from 1:1 to 1:16.7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study evaluated patients who were rapidly converted from intravenous opioids to methadone compared with those who were slowly converted. 27 The patients who had a successful rapid conversion to methadone received a methadone:fentanyl conversion ratio of approximately 2.5:1. Shaheen et al 28 demonstrated that conversion calculations are widely variable and require clinical judgment and patient-specific modifications to be used safely.…”
Section: Discussionmentioning
confidence: 99%